Anaerobic running capacity determined from a 3-parameter systems model: Relationship with other anaerobic indices and with running performance in the 800 m-run - Bosquet, L.; Delhors, P. R.; Duchene, A.; Dupont, G.; Leger, L. (International Journal of Sports Medicine, 2007)
The purpose of this study was to compare anaerobic running capacity (ARC, i.e., the distance that can be run using only stored energy sources in the muscle) determined from a 3-parameter systems model with other anaerobic indices and with running performance in the 800 m. Seventeen trained male subjects (V·O2max = 66.54 ± 7.29 ml · min-1 · kg-1) performed an incremental test to exhaustion for the determination of V·O2max and peak treadmill velocity (PTV), five randomly ordered constant velocity tests at 95, 100, 105, 110, and 120 % of PTV to compute ARC and oxygen deficit (O2def, at 110 % of PTV), and a 800-m time trial to determine running performance (mean velocity over the distance, V800 m) and peak blood lactate concentration ([La-]b, peak). ARC (467 ± 123 m) was positively correlated with O2def (56.35 ± 18.47 ml · kg-1; r = 0.57; p < 0.05), but not with [La-]b, peak (15.08 ± 1.48 mmol · l-1; r = - 0.16; p > 0.05). The O2 equivalent of ARC (i.e., the product of ARC by the energy cost of running; 103.74 ± 28.25 ml · kg-1), which is considered as an indirect estimation of O2def, was significantly higher than O2def (p < 0.01, effect size = 1.99). It was concluded that ARC is partially determined by anaerobic pathway, but that it probably does not provide an accurate measure of anaerobic capacity, if, however, O2def can be considered as a criterion measure for it.